2006
DOI: 10.1021/ie060214a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Structural Characterization of Calcium-Based Sorbents Calcined under Subatmospheric Conditions for the High-Temperature CO2Capture Process

Abstract: The influence of several process parameters on the calcination of a naturally occurring limestone and a precipitated mesoporous calcium carbonate (CaCO3) sorbent structure to calcium oxide (CaO) is detailed in this study. CaCO3 calcination is an integral part of a multicyclic carbonation−calcination reaction (CCR) process that separates carbon dioxide (CO2) from high-temperature gas mixtures into a pure CO2 stream. Maintenance of high sorbent reactivity over repeated CCR cycles reduces the capital and operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 19 publications
0
42
0
1
Order By: Relevance
“…However, steam partial pressure in the carbonator, the residence time of the particles in the calciner and the carbonator, the presence of ash, sulphur and other minor species, and particle size are likely to also play significant roles. The temperature of the calciner can be decreased if the partial pressure of CO2 is reduced, thus minimising the extent of sorbent sintering upon cycling; the two simplest ways of doing this are by lowering the total pressure (Ewing et al, 1979;Alvarez and Abanades, 2005;Sakadjian et al, 2007) (see also the Endex process, Section 5.5) or by introducing steam into the calciner (Alvarez and Abanades, 2005;Wang et al, 2008;Wang et al, 2009). The main research areas for sorbent enhancement are doping of natural limestones with trace amounts of organic salts, the production of synthetic sorbents, the hydration of spent sorbent, and thermal pre-treatment; an ideal enhanced sorbent will display high mechanical strength while maintaining its reactive surface area over repeated cycling, without being prohibitively expensive -for economic assessments see work by…”
Section: Sorbent Performancementioning
confidence: 99%
“…However, steam partial pressure in the carbonator, the residence time of the particles in the calciner and the carbonator, the presence of ash, sulphur and other minor species, and particle size are likely to also play significant roles. The temperature of the calciner can be decreased if the partial pressure of CO2 is reduced, thus minimising the extent of sorbent sintering upon cycling; the two simplest ways of doing this are by lowering the total pressure (Ewing et al, 1979;Alvarez and Abanades, 2005;Sakadjian et al, 2007) (see also the Endex process, Section 5.5) or by introducing steam into the calciner (Alvarez and Abanades, 2005;Wang et al, 2008;Wang et al, 2009). The main research areas for sorbent enhancement are doping of natural limestones with trace amounts of organic salts, the production of synthetic sorbents, the hydration of spent sorbent, and thermal pre-treatment; an ideal enhanced sorbent will display high mechanical strength while maintaining its reactive surface area over repeated cycling, without being prohibitively expensive -for economic assessments see work by…”
Section: Sorbent Performancementioning
confidence: 99%
“…Gupta et al [11][12][13] have studied calcination and carbonation of precipitated calcium carbonate (PCC) sorbents for CO 2 capture, and found that PCC had higher reactivity than CaO obtained from the calcination of naturally occurring limestone. However, the production process of PCC is compli- [14] utilized steam hydration of CaO to increase both the pore area and volume, as well as improving the long-term performance of the sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of porosity would lead to a high CO 2 partial pressure in the particle pores, slowing the rate of calcination in the particle interior. Hence, higher porosity leads to an increase in calcination rate, whereas higher pressure decreases the calcination rate (Sakadjian et al, 2007).…”
Section: Calcination Kineticsmentioning
confidence: 99%
“…The overall rate of calcination appears to be mass transfer limited and depends on how quickly CO 2 can be removed from the surface of the particle, rather than on the kinetics of CaCO 3 decomposition (Britton, Gregg, & Winsor, 1951;Maskill & Turner, 1932;Sakadjian, Iyer, Gupta, & Fan, 2007). CO 2 evolves from the CaCO 3 particle surface, as well as from the particle interior, from where it would have to diffuse out through pores in the particle, as indicated in Figure 16.4.…”
Section: Calcination Kineticsmentioning
confidence: 99%